2016
DOI: 10.1373/clinchem.2016.257485
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Rhythm of Cardiac Troponin: Consequences for the Diagnosis of Acute Myocardial Infarction

Abstract: 1. Circadian Variation of Cardiac Troponin, NCT02091427, www.clinicaltrials.gov/ct2/show/NCT02091427. 2. Advantageous Predictors of Acute Coronary Syndrome Evaluation (APACE) Study, NCT00470587, www.clinicaltrials.gov/ct2/show/NCT00470587.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
3
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 29 publications
4
64
3
19
Order By: Relevance
“…The mechanism of chronic cardiac troponin release is not elucidated, but recent observations suggest differences in release patterns of cardiac troponin T and I. [36] Third, postrelease modification such as fragmentation, complex formation, and elimination of cardiac troponins may differ between both cardiac troponins. [37,38] …”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of chronic cardiac troponin release is not elucidated, but recent observations suggest differences in release patterns of cardiac troponin T and I. [36] Third, postrelease modification such as fragmentation, complex formation, and elimination of cardiac troponins may differ between both cardiac troponins. [37,38] …”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation may be related to the rhythmic diurnal variation of hs-cTnT, which shows higher levels in the morning and at nighttime and lower levels during the day. [22][23][24] While rhythmic diurnal variation is characteristic for hs-cTnT, it has not been observed in hs-cTnI.…”
Section: Difference Between Hs-ctnt and Hs-ctnimentioning
confidence: 99%
“…Furthermore, since cTnI and cTnT are present in the sarcomeric complex in a molecular ratio of 1:1, these differences between the circulating cTns are probably related to differences in intra- [130] or extra-cellular [131][132][133] catabolism and the peripheral turnover of cTnI and cTnT. A recent study [134] found that circulating levels of cTnT, unlike cTnI, have a diurnal rhythm, thus bearing out the hypothesis that there are some differences in the release from cardiomyocytes and/or peripheral turnover between cTnI and cTnT.…”
Section: Do Differences In Troponin-dependent 99th Url Values Depend mentioning
confidence: 99%